Environmental Assessment Using Integrated Risk Based Approach (IRBA) at Cahaya Kencana Landfill Site - Muhammad Sadiqul Iman; Ellina Sitepu Pandebesie (Institut Teknologi Sepuluh Nopember, 2020)
Cahaya Kencana landfill site located above the land belonging to the local government of Banjar District with land area 35,5 Ha, where used for Cahaya Kencana landfill 16,5 Ha, Kehati park 7,5 Ha, the remaining unused land is 11,5 Ha. Cahaya Kencana landfill site has been implementing the sanitary landfill system since 2014 with the existing area of 8.089,73 m2 and the calculation results shows that sanitary landfill area can only use until the year 2021. So the goal that is to be achieved from this research is to evaluate the technical aspects and environment of Cahaya Kencana site with decision making tools. One of them through the assessment of environmental risk index or Integrated Risk Based Approach (IRBA). Risk Index (RI) assessment results using IRBA obtained 524,007 value with a category of moderate hazard evaluation, so that Cahaya Kencana site can be forwarded and rehabilitated into controlled landfill gradually. The strategy that needs to be done in the framework of Cahaya Kencana site is modifications of leachate treatment unit design.